2017
DOI: 10.3389/fimmu.2017.00394
|View full text |Cite
|
Sign up to set email alerts
|

Cross Talk between Inhibitory Immunoreceptor Tyrosine-Based Activation Motif-Signaling and Toll-Like Receptor Pathways in Macrophages and Dendritic Cells

Abstract: The innate immune cells sense microbial infection and self-ligands by pathogen recognition receptors (PRRs), such as toll-like receptors (TLRs) and regulatory receptors (RRs), associated with immunoreceptor tyrosine-based activation motif (ITAM). Rapid activation and concerted action of PRRs signaling and feedback inhibitory mechanisms must be engaged to ensure the host defense functions and to prevent cytotoxicity associated with excessive activation. ITAM-associated RRs can generate stimulatory or, paradoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 86 publications
3
38
0
Order By: Relevance
“…Dendritic cells also express TLR and FcR, and it is known that crosstalk occurs in these cells as well. However, the underlying molecular mechanisms and impact of crosstalk on immune function appear to be different (recently reviewed in 32 ). Future studies on the precise underlying molecular mechanisms in both cell types will yield exciting new insights.…”
Section: Discussionmentioning
confidence: 99%
“…Dendritic cells also express TLR and FcR, and it is known that crosstalk occurs in these cells as well. However, the underlying molecular mechanisms and impact of crosstalk on immune function appear to be different (recently reviewed in 32 ). Future studies on the precise underlying molecular mechanisms in both cell types will yield exciting new insights.…”
Section: Discussionmentioning
confidence: 99%
“…A novel role of miR‐210 has been uncovered in AS progression through regulating endothelial apoptosis (Li, Yang, Zhang, & Yang, ). Recently, miR‐182‐5p has demonstrated abnormal (Hirata et al, ; Hirata et al, ; Hirsch, Janovec, Stranska, & Bendriss‐Vermare, ). MiR‐182‐5p is observed to promote human prostate cancer development via targeting FOXF2, RECK and MTSS1 expression (Hirata et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In human bladder cancer, miR‐182‐5p can play an oncogenic role and inhibit Smad4 and RECK (Hirata et al, ). It is reported that miR‐182‐5p is highly upregulated in breast cancer samples (Hirsch et al, ). However, few studies are focused on AS progression, which encouraged us to study the function of miR‐182‐5p in the AS in the current study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the molecular events that allow separation of these two CEACAM3 effector functions remain unknown. Moreover, from a broader perspective, the molecular processes that allow synergy between ITAM‐containing phagocytic receptors and TLRs remain poorly defined (Hirsch, Janovec, Stranska, & Bendriss‐Vermare, ; Underhill, ). Although human neutrophils express CEACAM1, CEACAM6, and other receptors with the potential to mediate bacterial engulfment, CEACAM3 has been shown to act as the principle phagocytic receptor for N. gonorrhoeae (Schmitter et al, ).…”
Section: Resultsmentioning
confidence: 99%